Comparison of quality of life, anxiety, and satisfaction with rehabilitation services among mothers of children with autism spectrum disorders and those without autistic children in Ahvaz-Iran - Peyman Zamani; Hassan Khoramshahi; Nasrin Khosravi; Saeed Hesam (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2022)
Background. Mothers with autistic children suffer a lot of psychological and physical pressures that can affect their quality of life, emotional states, and judgment about medical services. This study aimed to evaluate the quality of life, anxiety, and satisfaction with rehabilitation services for mothers of children with autism spectrum disorders and of non-autistic children in Ahvaz-Iran. Methods. In this cross-sectional descriptive-analytical study, 128 mothers with autistic children and 30 mothers with non-autistic children needing rehabilitation interventions were selected from Ahvaz rehabilitation centers. All participants were asked to complete Quality of Life (WHOQOL-BREIF) questionnaire, 14-item Perceived Stress Scale as well as Satisfaction Questionnaire. Data analysis was performed using a multivariate three-way ANOVA test. Results. It was found that mothers of autistic children had a significantly lower quality of life score than those without autistic children (P<0.001). However, the two groups had no significant difference in anxiety score (P=0.114) and satisfaction (P=0.079). Factors such as age, education, and occupation of mothers significantly affected the results (P<0.05). Moreover, mothers whose autistic children received rehabilitation services under one month had lower quality of life (P=0.003) and a higher level of anxiety (P=0.025) than those who received rehabilitation over six months. Conclusion. Middle-aged housewives with autistic children had the lowest mean quality of life score among all mothers studied. Mothers with a university education reported a lower level of satisfaction compared to mothers without a university education, indicating a higher level of expectations for their rehabilitation outcome. Practical Implications. Research findings can be applied in managing rehabilitation services for autistic children and their families.